Care perception in nursing students: characterization and impact for the formation and vision of professionals (2010)
The results of the research: "Care perception of first semester nursing students at the National University of Colombia" during the period April to June 2007 are presented here. There are descriptions of the characteristics of care behaviors identified by students when answering a questionnaire Lickert scale type to which facial and content tests were applied. A theoretical analysis was carried out on the findings in their relation with nursing epistemology and the fundamental patters of knowing proposed by Carper. The sample consisted of 86 first semester students in the period April to June 2007, who had not had subjects of the disciplinary component, to control the risk of contaminating the sample. The results show that the care perception in first semester students of the Nursing Faculty from the National University of Colombia is focused on the care behaviors related with the empirical knowledge pattern, in other words, with the fundamentals of clinic and technical assistance for nursing care and what is inherent to the ethical pattern. The personal and esthetic patterns were perceived with less frequency, reason why the importance of educating students in the humanistic dimensions of care, stands out.